Estrogenic activity target endocrine disrupting chemical levels and potential health risks of bottled water and water from selected distribution points in Pretoria and Cape Town - De Jager, Christiaan (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2016.